Iron Metabolism in Prostate Cancer; From Basic Science to New Therapeutic Strategies - Vela, Driton (Frontiers in Oncology, 2018)
An increasing amount of research has recently strengthened the case for the existence of iron dysmetabolism in prostate cancer. It is characterized with a wide array of differential expression of iron-related proteins compared to normal cells. These proteins control iron entry, cellular iron distribution but also iron exit from prostate cells. Iron dysmetabolism is not an exclusive feature of prostate cancer cells, but it is observed in other cells of the tumor microenvironment. Disrupting the machinery that secures iron for prostate cancer cells can retard tumor growth and its invasive potential. This review unveils the current understanding of the ways that prostate cancer cells secure iron in the tumor milieu and how can we exploit this knowledge for therapeutic purposes.